Selective activation of functional suppressor cells by human seminal fluid. - Witkin, S S (1986)
The ability of seminal fluid (SF) to induce suppressor cell activity from peripheral blood mononuclear cells (PBMN) was examined. PBMN were incubated with SF for 48 h, washed to remove SF components, treated with mitomycin C (mit C) and co-cultured with Raji cells, a lymphoblastoid cell line. Raji cell proliferation was inhibited by SF-treated PBMN proportionally to SF concentration. SF (50-200 micrograms), mit C-treated Raji cells or mit C-treated PBMN pre-incubated with phytohaemagglutinin were without effect on Raji cell growth. Suppressor T lymphocytes generated by incubation of PBMN with concanavalin A inhibited Raji cells to the same extent as did SF-treated PBMN. All activity was lost following heating at 56 degrees C for 30 min; freezing and thawing reduced the ability of SF to induce suppression by 50%. Dialysis of SF or treatment with antibody to prostaglandin E2 led to a 50% reduction in suppression.